2015
DOI: 10.3126/ajms.v6i5.11782
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary dysfunction in children with beta thalassemia major in relation with iron overload - a cross sectional hospital based study

Abstract: Background: Previously many patients with thalassemia major died from severe anemia during first decade, but with modern transfusion therapy many now survive beyond childhood. Because of such therapy, however excessive iron deposition occurs in lungs and causing respiratory dysfunction. Respiratory impairment occurs because of defective chelation and repeated transfusions. Objectives: To a) study pattern of respiratory impairment using spirometry, b) estimate iron overload by measuring serum ferritin levels, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Several studies confirmed the correlation between serum ferritin or the body iron burden and pulmonary dysfunctions (Kanj et al, 2000;Carnelli et al, 2003). However, this contradicted with other studies (Li et al, 2002;Boddu et al, 2015). The discrepancy of the results among the studies could be due to the multifactorial causes of pulmonary dysfunctions in thalassemic patients.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Several studies confirmed the correlation between serum ferritin or the body iron burden and pulmonary dysfunctions (Kanj et al, 2000;Carnelli et al, 2003). However, this contradicted with other studies (Li et al, 2002;Boddu et al, 2015). The discrepancy of the results among the studies could be due to the multifactorial causes of pulmonary dysfunctions in thalassemic patients.…”
Section: Discussionmentioning
confidence: 90%
“…Thirty-five (70%) thalassemic children had isolated or combined PFT abnormalities. Many studies addressed the pulmonary functions in children with -thalassemia major, reporting percentages of pulmonary dysfunction ranging between 36·1 and 95% (Arora et al, 2001;Abu-Ekteish et al, 2007;Parakh et al, 2007;Rahim et al, 2008;Eidani et al, 2009;Alyasin et al, 2011;Boddu et al, 2015;Ozyoruk & Misirlioglu, 2015). This wide range of percentages may be attributed to the measurement of lung volumes and diffusion capacities, beside spirometry, in some studies and the use of spirometry alone in others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Konsekuensi perubahan ini berupa penurunan atau hilangnya mRNA untuk satu atau lebih rantai goblin atau tidak efektifnya pembentukan mRNA. 13 Gangguan fungsi paru pada pasien talasemia β mayor telah diketahui dalam tiga dekade terakhir meskipun sampai saat ini mekanisme patogenesisnya belum sepenuhnya diketahui. Berbagai variasi gangguan fungsi paru ditemukan pada pasien talasemia β mayor berupa gangguan fungsi paru restriktif, obstruktif, dan atau campuran.…”
Section: Pembahasanunclassified